The Effect of Mental Health and Psychosocial Support Interventions on Depression, Anxiety, and Stress in Children with Physical Disabilities - Adristi, Nala Duhita Adristi; Maghfiroh, Fitrania; Rakasiwy, Mochamad Randy Pradika; Andjanie, Nindya Wahyu Hening; Satwika, Yohana Wuri (Universitas Ahmad Dahlan, 2025)
This study investigated the effectiveness of Mental Health and Psychosocial Support (MHPSS) interventions in reducing depression, anxiety, and stress among children with physical disabilities. The intervention program integrated relaxation techniques, emotional literacy, and peer-based activities to promote adaptive coping and emotional resilience. A pretest–posttest design was employed, and statistical analysis indicated a significant improvement in psychological well-being, with large effect sizes across all variables. The greatest change occurred in depressive symptoms, followed by reductions in anxiety and stress levels. These findings suggest that structured and contextually adapted MHPSS programs effectively enhance emotional regulation and psychosocial adjustment. The study highlights the importance of school-based psychosocial initiatives in fostering inclusive education and reducing stigma toward children with disabilities.